2012
DOI: 10.1119/1.3697837
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the motion of a loaded hoop

Abstract: We report the results of an experiment on the rolling motion of a loaded hoop. The data are obtained using a high-speed video camera, and the motion is analyzed on a frame-by-frame basis. Our analysis demonstrates that the experimental results are in reasonably close agreement with previously reported theoretical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
3
10
0
Order By: Relevance
“…3,4 Lately, they experimentally confirmed that their model captures the essential aspects of the motion of an asymmetric hoop on a horizontal plane. 5 In a similar way, Taylor and Fehrs verified Theron and Maritz' theoretical predictions regarding the hopping conditions, 7 as well as Gómez et al based on an independent model. 8 In all the aforementioned papers, particular attention was devoted the case of highly eccentric bodies (γ > 0.5) in descending or horizontal motions, as this favors the interesting hopping phenomenon, but the intriguing upward motion was not analyzed.…”
Section: If the Disk Rises In What Way Does It And How Far Can It Go?supporting
confidence: 62%
See 2 more Smart Citations
“…3,4 Lately, they experimentally confirmed that their model captures the essential aspects of the motion of an asymmetric hoop on a horizontal plane. 5 In a similar way, Taylor and Fehrs verified Theron and Maritz' theoretical predictions regarding the hopping conditions, 7 as well as Gómez et al based on an independent model. 8 In all the aforementioned papers, particular attention was devoted the case of highly eccentric bodies (γ > 0.5) in descending or horizontal motions, as this favors the interesting hopping phenomenon, but the intriguing upward motion was not analyzed.…”
Section: If the Disk Rises In What Way Does It And How Far Can It Go?supporting
confidence: 62%
“…Although the analysis of the motion of asymmetric rigid bodies is not new in the literature [2][3][4][5][6][7], our treatment is complementary in both methodology and results. Previously, Carnevali and May [5] investigated a similar problem from a Lagrangian point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We must also express our admiration for the students who answered Webb's question correctly 2. Other demonstrations can be found in[13][14][15].…”
mentioning
confidence: 92%
“…The topics of Uniform Circular Motion (UCM) and Uniformly Accelerated Circular Motion (UACM) are present in all teaching levels of Physics and pave the ground for the study of more complex rotational motions. There are several experiments reported on this topic [16][17][18][19][20][21][22]. For instance, a technique based on 3D video photogrammetry has been used for analyzing a rigid body [19], and the motion of a loaded hoop is studied by using a high-speed video [20].…”
Section: Introductionmentioning
confidence: 99%